Performance comparison and analysis of TCP-Friendly Rate Control (TFRC) over the network - Mohamad Izril, Ishak
This project proposes a Performance Comparison and Analysis of TCP-Friendly Rate Control (TFRC) over the network. Generally, TFRC is used for carrying real-time data. Traditionally, real-time data transmission has been accomplished over the user datagram protocol (UDP). The challenging issues of using Transport Control Protocol (TCP) are restrictive bandwidth and lagging. Additionally, it is widely known that TCP is ill-suited to real-time multimedia streaming application. Having known these issues, this project aims to study the possibilities for analysis and improvement of real-time data application using TFRC which is designed for long-lived streams. As known, there are many advantages of TFRC, which are congestion control and guaranteeing the required throughput. Therefore, this project explores and proposes the advantages of TFRC in transmitting and receiving real-time data. It is proposed that the investigation of TFRC in real-time data is conducted using simulation technique. During the simulation, the developed model is representing the real-time application for analyzing the performance of modified TFRC. The modified TFRC mechanism is introduced as TFRC proposed scheme and evaluated through the simulation experiment. The simulation study of this project is to analyze and evaluate some parameters of existing TFRC mechanisms. The performance analysis and simulation experiment show that the proposed scheme performs better compared to the other mechanisms involved. The results of applying the proposed scheme outperform the other mechanisms up to 5% for throughput efficiency and up to 20% on packet loss. Finally, this study has possibilities of the ongoing work to be carried for implementing in wireless environment and IPv6.